Method of measurement of the dynamic strength of concrete under explosive loading - Garkushin, Gennady V.; Kanel, Gennady I.; Razorenov, Sergey V.; Savinykh, Andrey S. (International journal of fracture)
Within the framework of the search for the method of determination of the strength properties of concrete under the action of an explosion or high-velocity impact, suitable for large scale concrete samples, the evolution of the compression pulse in plates or rods made of concrete with compressive strength of 30 MPa was investigated. It was found that wave configuration consisting of the ramped elastic precursor with insignificant stress jump at the front followed by a dispersed plastic shock wave is formed in the plates under uniaxial shock compression. In this experimental configuration, the compressive strength of the material is not identified. Experiments with concrete rods of various diameters have demonstrated the scalability of the wave process. It was established that the compressive fracture of the rods occurs at a distance of around twice their diameters and is accompanied by the fast decay of the load pulse after that weakly decaying elastic wave was propagated along the rods. The measurements of parameters of the compression pulse at the end of the fracture zone allowed us to determine the value of the dynamic compression strength of concrete equal to 105±20 MPa , which turned out to be 3.5 times higher than the static strength.